The effects of multimarket contact on partner selection for technology cooperation - Ryu, Wonsang; Reuer, Jeffrey J.; Brush, Thomas H. (Strategic Management Journal, 2020)
Research summary We investigate how multimarket contact between prospective partners affects their partner selection for technology cooperation. Drawing on the multimarket competition literature, we argue that multimarket contact generates mutual forbearance from opportunism by enabling broad retaliation across the shared markets against opportunism. As a result, multimarket contact between potential partners makes them prefer each other as partners for technology cooperation. We also claim that this positive effect of multimarket contact on the formation of cooperative agreements is more pronounced when the partners have reciprocal contacts rather than nonreciprocal ones. Managerial summary This article explains one of the reasons why rival firms can be good partners to each other for technology cooperation. Managers might conjecture that firms tend to avoid partnering with rival firms for R&D because they may be more opportunistic than those without product market overlap. However, our theory suggests a counter‐intuitive argument that market overlap between partners rather deters them from engaging in opportunistic behaviors because market overlap enables them to broadly retaliate against such behaviors across the shared product markets. Consistent with this idea, our empirical results show that global top 200 biopharmaceutical companies are more likely to choose each other for technology cooperation as they share more product markets and this tendency is reinforced when their important markets are different.